High Temperature Corrosion Behavior of Stellite 6 Coated Superalloy in Gas Turbine Environment - Sharma, Shrutika (My University, 2021)
Degradation by high-temperature oxidation, hot corrosion and erosion are the main failure modes of components in the hot sections of gas turbines, boilers, industrial waste incinerators, metallurgical furnaces, petrochemical installations, etc. Protective coatings are often applied on metal substrates to prevent electrochemical charges present in corrosive environment from entering inside metal substrate. When corrosive environment comes in contact with protective coating, the coating forms layer of oxides that provide a barrier against corrosive species and higher the thickness of coating, the stronger is the barrier between corrosive species and metal substrate. In this way, the metal substrate stays protected from the corrosive environment. In this work, efforts have been made to enhance the life of Superni 600 by deposition of Stellite 6 coating by detonation gun thermal spray technique. The coated and uncoated Superni 600 samples were exposed to molten salt solution of Na2SO4–60%V2O5 upto 25 cycles to observe the hot corrosion behaviour of the samples. It was observed that formation of cobalt based oxides on coated samples helped in improving the corrosion resistance of Superni 600. Although, it seems that oxides of Stellite 6 coating in gas turbine environment get degraded with subsequent cycles but will surely enhance the life of substrate as the coating remains intact even after 25 cycles of corrosion run.
Keywords: Stellite 6 coating; D-gun; Superni 600; Corrosion; Superalloys